Mucosa-associated lymphoid tissue lymphoma arising from the kidney - Niwa, Naoya; Tanaka, Nobuyuki; Horinaga, Minoru; Hongo, Hiroshi; Ito, Yujiro; Watanabe, Takuro (Canadian Urological Association Journal, 2014)
Primary renal lymphoma is rare, and most are intermediate- and high-grade lymphomas of B-cell lineage, such as diffuse large B-cellor Burkitt lymphoma. We report a case of low-grade B-cell lymphoma of the mucosa-associated lymphoid tissue (MALT) arising from the kidney. Only a few cases of primary renal MALT lymphoma have been published.